Social representation of intercultural exchange in an international university. Issue 2 (3rd March 2016) - Kudo, Kazuhiro
Abstract : This paper provides an interpretive investigation into the social representation of intercultural exchange at one of the newly established international universities in Japan. The author conducted quasi-structured interviews with 5 staff members and 22 students to gain insight into their perceptions of intercultural exchange and interactions. The findings highlight the dominance of nation-bound and instrumental representations of interculturality, and suggest the importance of integrating intercultural interaction issues into formal curriculums while celebrating intercultural connectivity, interchange and hybridity in both institutional and interpersonal levels.